2011
DOI: 10.1111/j.1600-6143.2011.03677.x
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance Protocol Kidney Transplant Biopsies: Their Evolving Role in Clinical Practice

Abstract: Protocol renal allograft biopsies at fixed time points from transplantation have aided research and provided insights into the pathogenesis of early and late allograft injury. Their role is evolving from research to a clinical management tool needed to detect subclinical pathology requiring treatment adjustment. They frequently reveal unexpected findings and influence therapy in the majority of patients. Detection of subclinical rejection (SCR) remains important despite declining prevalence with triple therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 53 publications
1
50
0
1
Order By: Relevance
“…In specific populations, for example, high-risk patients with cross-match-positive transplantation, with de novo DSA, or at high risk of glomerular disease recurrence, surveillance biopsies could thus be warranted in the absence of proteinuria or graft dysfunction, for the timely detection of subclinical injury. 22 In this light, it seems surprising that the presence or occurrence of DSA did not independently associate with proteinuria in our study, which is in agreement with two recent studies. 23,24 Although the number of patients positive for DSA was low in our cohort and the data should thus be interpreted cautiously, it could be hypothesized that the presence of DSA does not lead to proteinuria per se, but that proteinuria appears only if DSA cause glomerular injury.…”
Section: Discussionsupporting
confidence: 81%
“…In specific populations, for example, high-risk patients with cross-match-positive transplantation, with de novo DSA, or at high risk of glomerular disease recurrence, surveillance biopsies could thus be warranted in the absence of proteinuria or graft dysfunction, for the timely detection of subclinical injury. 22 In this light, it seems surprising that the presence or occurrence of DSA did not independently associate with proteinuria in our study, which is in agreement with two recent studies. 23,24 Although the number of patients positive for DSA was low in our cohort and the data should thus be interpreted cautiously, it could be hypothesized that the presence of DSA does not lead to proteinuria per se, but that proteinuria appears only if DSA cause glomerular injury.…”
Section: Discussionsupporting
confidence: 81%
“…clinical allograft rejection) decreased to 10-15% using tacrolimusbased immunosuppression (2), subclinical rejection including borderline changes occurs in 10-30% of patients within the first year posttransplant (3)(4)(5)(6). As persisting subclinical rejection is associated with progression to chronic irreversible damage and slow deterioration of allograft function (5,(7)(8)(9), its detection is important allowing for timely therapeutic interventions (10).…”
Section: Introductionmentioning
confidence: 99%
“…10 Other authors have suggested the use of biopsies to detect subclinical rejection. 11,12 A total of 61 biopsies were analyzed and the following oxidative stress enzymes were detected by Western blot: catalase (60 kilodaltons), MnSoD (25 kilodaltons), CuZnSoD (23 kilodaltons), thioredoxin reductase (55 kilodaltons), thioredoxin (2b1) (12 kilodaltons), and thioredoxin (62 kilodaltons).…”
Section: Discussionmentioning
confidence: 99%